Kohonen map modification for classification tasks - Jelínek, Jiří (SciTePress, 2019)
This paper aims to present a classification model based on Kohonen maps with a modified learning mechanism and structure as well. Modification of the model structure consists of its modification for hierarchical training and recall. The change of the learning process is the transition from unsupervised to supervised learning. Experiments were performed with the modified model to verify changes in the model and compare the results with other research.
Keywords: Kohonen Map; Neural Networks; Pattern Classification